The Influence of Human Resource Quantity on Service Quality - Fikriyatul Hasanah; Muh. Darwis; Nasir Nasir; Asmansyah Asmansyah (Journal of Public Policy and Local Government (JPPLG), 2025)
Globalization and the development of information technology require government agencies to improve public services as a whole so that people expect satisfactory service according to their rights as citizens. This study aims to analyze the influence of the quantity of human resources on the quality of service at the Tamalanrea District Office, Makassar City. The method used is a quantitative approach with data collection techniques in the form of questionnaire distribution, observation, and documentation. The study population was 59 employees with a sample of 51 respondents based on the Krejcie and Morgan tables. The data was analyzed using descriptive and inferential statistics processed with the help of SPSS and Microsoft Excel software. The findings of this study reveal that (1) the quantity of human resources is in the sufficient category, (2) the quality of service is in the good category, and (3) there is a significant influence between the quantity of human resources on the quality of service with a significance value of 0.000 with a Pearson Product Moment correlation of 0.525, which shows a moderate relationship (relative relation) between the quantity of human resources and the quality of service. The t-test results, with a magnitude of 4.315 greater than tcount > ttable 2.010, validate this finding, leading to its acceptance. The hypothesis indicates a significant influence between the quantity of human resources and the quality of service. The magnitude of the influence only reached 27.5% based on the value of the determination coefficient (R²), while the rest was influenced by other factors that were not specifically explained in this study.